Annealing-induced interfacial atomic intermixing in InAs/GaSb type II superlattices - Li, Xiaochao; Zhang, Yong; Jiang, Dongwei; Guo, Fengyun; Zhao, Liancheng (Applied physics letters, 2017)
We have investigated the effect of post-growth rapid thermal annealing (RTA) on the interface structure and atomic intermixing of InAs/GaSb type II superlattices (T2SLs). It is found that the mechanism of interfacial atomic interdiffusion of the anion (In/Ga) and the cation (As/Sb) is different. The activation energies of 0.62 eV and 0.27 eV are calculated to describe the In/Ga and As/Sb interdiffusion. In T2SLs, RTA will promote As/Sb intermixing across the interfaces between 450 and 480 °C, while In/Ga intermixing will be activated at 500 °C annealing. This demonstrates that the appropriate In/Ga intermixing is important to control the deterioration of the interfacial quality and the formation of dislocations, which is very crucial for the device performance.